Workshop Pengembangan Evaluasi Berbasis Teknologi dengan Real-Time Feedback - Irham Irham; Aiyub Aiyub; Gustina Fitri; Syaifuddin Syaifuddin; Munardy Munardy; Riyadhsyah Riyadhsyah; Miswar Miswar (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The advancement of educational technology has transformed learning evaluation systems into more interactive, participatory, and data-driven approaches. One platform that supports real-time feedback is Kahoot!, which enables lecturers to obtain instant assessment results through game-based quizzes. This community service program aimed to enhance lecturers’ competencies in designing and implementing technology-based learning evaluation using Kahoot! with real-time feedback features. The program was conducted through a participatory hands-on workshop. The results indicate improved understanding of digital formative assessment, enhanced ability to design interactive Kahoot!-based quizzes, and strengthened skills in analyzing real-time evaluation data to improve teaching practices. The activity contributes to strengthening lecturers’ digital literacy and interactive learning implementation in the digital transformation era.